Electrochemical response of ZrCN-Ag-a(C, N) coatings in simulated body fluids. (10th September 2015) - Calderon, S.; Cavaleiro, A.; Carvalho, S.
Abstract: In this study, Zr-C-N-Ag coatings were deposited by magnetron sputtering aiming to provide an enhanced corrosion resistance to stainless steel 316 L, while adding antibacterial capabilities using silver, a well-known antibacterial agent. The films were analysed by X-ray diffraction, Raman spectroscopy, electron probe microanalysis and X-ray photoelectron spectroscopy (XPS) in relation to the chemical composition and structural characteristics. Additionally, electrochemical impedance spectroscopy and potentiodynamic tests were carried out as a function of the immersion time, in Hanks' balanced salt solution with 10 g/L of Bovine serum albumin (BSA), to evaluate the electrochemical characteristics of the samples. The results revealed that the coatings are predominantly composed by ZrCx N1−x, Ag and amorphous carbon phases. A large deterioration of the electrochemical stability of the films was evidenced as the silver content increased. The presence of amorphous carbon phases negatively influenced the polarization resistant, behavior ascribed to morphological changes. The immersion test showed a progressive increment of the polarization resistance with time, attributed to surface and pores passivation, due to the formation of both ZrO2 and albumin protective layers on the surface, as shown by XPS.